2012
DOI: 10.1246/cl.2012.498
|View full text |Cite
|
Sign up to set email alerts
|

Pd-complex-bound Amino Acid-based Supramolecular Gel Catalyst for Intramolecular Addition–Cyclization of Alkynoic Acids in Water

Abstract: An NCN-pincer Pd-complex-bound norvaline-based supramolecular gel showed efficient catalytic activities for the intramolecular addition–cyclization of alkynoic acid and phenol derivatives in water to afford the corresponding ene-lactones in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Significant changes in and enhancement of the original properties, functions, and performance can be induced by cooperative interactions of arrayed functionalities in well‐ordered nanosized hierarchical architectures. In practice, arrayed functional groups fabricated from functionalized amino acids and peptides bearing conjugated with photoactive,54 electronically active,55 and catalytically active37b, 56 auxiliaries have been reported as examples of such advanced supramolecular functional materials that show enhanced performance or emergent properties not accessible by unimolecular systems. Metalated amino acids and peptides that conjugate with functional organometallics have potent abilities as such supramolecular materials; however, little research on such peptides has been reported as yet.…”
Section: Resultsmentioning
confidence: 99%
“…Significant changes in and enhancement of the original properties, functions, and performance can be induced by cooperative interactions of arrayed functionalities in well‐ordered nanosized hierarchical architectures. In practice, arrayed functional groups fabricated from functionalized amino acids and peptides bearing conjugated with photoactive,54 electronically active,55 and catalytically active37b, 56 auxiliaries have been reported as examples of such advanced supramolecular functional materials that show enhanced performance or emergent properties not accessible by unimolecular systems. Metalated amino acids and peptides that conjugate with functional organometallics have potent abilities as such supramolecular materials; however, little research on such peptides has been reported as yet.…”
Section: Resultsmentioning
confidence: 99%
“…Although in a limited number of examples (only six substrates were explored), the group of Nakamura also demonstrated the capacity of the NCN-pincer Pd(II) derivative 7 ( Figure 1) to promote the high-yield formation of five-membered ring lactones from both γ-and β-alkynoic acids (5-exo-dig and 5-endo-dig cyclization, respetively) in pure water [33]. Complex 7 easily generates hydrogen-bonding-based supramolecular gels, with well-organized Pd-arrays, in organic solvents.…”
Section: Cycloisomerization Of Preformed or In Situ Generated Alkynoimentioning
confidence: 99%
“…Some supramolecular gel catalysts that catalyze the oxidation of alcohols, hydrolysis of esters, aldol reactions and intramolecular cycloaddition of alkynoic acids have recently been reported. 25,[36][37][38] These reports showed the potential applicability of supramolecular gels as catalysts, although they did not mention the differences between the reaction kinetics in the gel phase and in solution. The supramolecular gel of 1 with an excess amount of Pd (OAc) 2 contains free Pd(OAc) 2 in the supramolecular gel phase.…”
Section: Wacker Oxidation In Supramolecular Gelmentioning
confidence: 99%